Exploring the relationship between facilitating factors and adherence to nursing ethical standards - Shima Bordbar; Gholamhossein Mehralian; Fatemeh Rezabeigi Davarani; Ali Reza Yusefi (BMC Nursing)
Abstract Background Professional ethics is a cornerstone of the nursing profession, with its observance closely linked to the enhancement of nursing services and the satisfaction of service recipients. This study aimed to assess nurses’ compliance with professional ethical codes and its relationship with factors that facilitate such compliance. Methods This descriptive-analytical, cross-sectional study was conducted in 2021 in a hospital located in southern Iran. A total of 312 nurses were selected using the census method and participated in the study. Data were collected through researcher-designed questionnaires that assessed compliance with professional ethical codes and factors facilitating such compliance. Data analysis was conducted using SPSS software version 23, employing t-tests, ANOVA, Pearson’s correlation coefficient, and multiple linear regression. Results The mean scores for compliance with professional ethical codes and factors facilitating compliance were 127.94 ± 8.52 (out of 170) and 98.31 ± 6.22 (out of 180), respectively. Nurse-related factors (β = 0.323, p < 0.001), patient-related factors (β = 0.286, p = 0.002), and management factors (β = 0.277, p = 0.003) emerged as significant predictors of compliance with professional ethical codes. Significant differences in compliance scores were observed based on gender (p = 0.01), marital status (p = 0.02), level of education (p = 0.04), and the number of patients under observation per work shift (p = 0.03). Additionally, the mean score of factors facilitating compliance with ethical codes was higher among female nurses (p = 0.03) compared to male nurses. Conclusion Compliance with professional ethical codes was rated as acceptable, while the factors facilitating compliance were rated as moderate. Given the predictive role of facilitating factors, targeted improvements in these areas could significantly enhance nurses’ adherence to professional ethical codes.